2018
DOI: 10.4103/ccd.ccd_155_18
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro study to evaluate and compare the flow property of different commercially available zinc oxide eugenol impression materials

Abstract: Introduction:Impression making is one of the most important steps in prosthodontic rehabilitation of edentulous patients. Zinc oxide eugenol (ZOE) impression paste is the most commonly used material for complete denture wash impression due to its cost-effectiveness and ease of manipulation, while providing the advantage of ability to record fine minute tissue details. Rheological property like flow is a critical factor influencing the success of any impression material, especially in intraoral conditions. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…This could be attributed to the incorporation of water at 10°C and higher activation energy at 40°C and 50°C, leading to a rapid increase in viscosity, thus, limiting the spread of the material under load. [ 23 24 ] However, better consistency was observed at 40°C and 50°C compared to 10°C. Although the material showed a faster setting, an increase in the consistency can be attributed to the plasticizing component such as thermoplastic substances present in the material.…”
Section: Discussionmentioning
confidence: 98%
“…This could be attributed to the incorporation of water at 10°C and higher activation energy at 40°C and 50°C, leading to a rapid increase in viscosity, thus, limiting the spread of the material under load. [ 23 24 ] However, better consistency was observed at 40°C and 50°C compared to 10°C. Although the material showed a faster setting, an increase in the consistency can be attributed to the plasticizing component such as thermoplastic substances present in the material.…”
Section: Discussionmentioning
confidence: 98%
“…Curcumin had no critical impact on quercetin-actuated atomic DNA harm, lipid per oxidation and protein corruption and along these lines has the one of a kind capability of going about as both master and cancer prevention agents, contingent upon the redox condition of their organic condition. Broad in vitro and in vivo testing has demonstrated that turmeric restrains synthetically incited epidermal ornithine decarboxylase action, epidermal DNA union, and the advancement of skin tumors in mice 16 .…”
Section: Discussionmentioning
confidence: 99%